Preferred learning styles among first year diploma students using fuzzy logic system / Nur Rusmawati Ishak - Ishak, Nur Rusmawati (2021)
Every individual has his or her own natural or habitual pattern of gathering and processing information in learning situations. The different environments between school and university will pose a significant impact on the learning style of students. The objectives of this study are to analyse the most preferred learning style among first-year diploma students in Universiti Teknologi MARA (UiTM) Arau, Perlis and to compare the preferred learning style by male and female students using Fuzzy Logic System. There were nine variables inputs in determining the fuzzy logic learning styles which are reading likeness, by nature, thinking time, speaking rate, activity level, activity enjoyment, visual distraction, auditory distraction and using instruction to obtain the VARK learning styles output. The result shows that 40% of the students preferred visual learning styles based on the VARK questionnaire while for fuzzy inferences system, 32% of the students preferred visual learning styles. Therefore, the visual learning style is chosen as the most preferred learning styles among the students in UiTM Perlis.